The Influence of Experiental Learning Model Based on Creative Industry to the Learning Achievement of Creative Products and Entrepreneurship Lesson in Vocational Highschool - Singgih Prastawa; Mey Ester Marbun (P3M IAI Nusantara Batang Hari, 2024)
This study aims to determine the effect of learning using Experiential learning model based on creative industry with conventional learning in Creative Product and Entrepreneurship subject in Vocational High School (VHS). This type of research is experimental research, a quasi type with pre-test and post-test group design. The population in this study of the subjects were Vocational High School Students (VHS) in Surakarta at school year of 2023/2024. Data collection methods in this research used observation, questionnaire, test and document analysis. Data analysis of this study used descriptive analysis and inferential analysis. Tests used the t test, before the implementation of the t test, there was a prerequisite test that was normality and homogeneity test, continued the balance test using the t test in the pre-test of the control group and the Experiment group. The result showed that there were significant differences in the mastery of knowledge competencies in Creative Product and Entrepreneurship lessons between students taught using Experiential learning models based on creative industries compared to students taught using conventional methods. The results are shown by t count 6.40 > t table 2.002, while for p value 0.00 <0.05. The conclusion is learning using Experiential learning models based on creative industries has an effect on learning outcomes for students in Creative Product and Entrepreneurship lessons in VHS.